Pemanfaatan Teknologi Big Data dalam Penyusunan RPJMDesa di Desa Ulak Kerbau Baru - Lionardo, Andries; Putra, Raniasa; Adam, Ryan; Fathuurrahmaan, Amma; Ivana, Ivana; Syafebri, Arrahman; Saleh, Hatta. M (Penerbit Goodwood, 2026)
Purpose: This study aims to support the government of Ulak Kerbau Baru Village in modernizing the preparation of its Medium-Term Village Development Plan (RPJMDes) through Big Data technology to enhance participatory, transparent, and evidence-based planning. Methodology/approach: The program took place in Ulak Kerbau Baru Village, Tanjung Raja District, Ogan Ilir Regency. Activities included training, technical assistance, and digital community surveys. The tools used were laptops and Android smartphones, while the main software comprised Google Forms, Google Data Studio, QGIS 3.28 Firenze, Microsoft Excel 2021, SPSS 26, and NVivo 12 Plus. Results/findings: The initiative improved the digital data management skills of village officials and increased community participation, with 215 respondents engaging in online surveys. A data-driven RPJMDes was produced, supported by thematic maps and interactive dashboards. NVivo analysis revealed five dominant community priorities: road infrastructure, agriculture, digitalization, education, and health. Conclusions: Integrating Big Data into village planning enhances transparency, accountability, and evidence-based governance. The approach also fosters stronger community engagement and provides a replicable model for other villages with similar characteristics. Limitations: The study was limited by inadequate internet infrastructure and its focus on a single village, which restricts broader generalization. Contributions: This research advances participatory governance and rural planning by demonstrating practical Big Data applications at the village level, offering a model for policymakers and local governments to strengthen data-driven decision-making in rural contexts.